INSTITUTE OF THE PRESIDENT OF UKRAINE IN THE CONTEXT OF POLITICAL CRISIS 2004 AND 2013-2014: FACTORSOF INFLUENCE AND TRANSFORMATION - Moskaliuk, M. F. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2018)
The article analyzes the specifics of the transformation of the national Presidency against the background of important social and resonant events of the early twenty-first century: The Orange Revolution and the Revolution of Dignity. A political analysis of presidential election campaigns in 2004 and 2014 has been carried out. It has been proved that the change in the form of the republican government in Ukraine and the powers of the head of state during this period took place in the context of political crises and the consequences of the orange and eurointegration squares. Particular attention is paid to the evolution of the constitutional and legal status of the President of Ukraine in the conditions of the presidential-parliamentary and parliamentary-presidential republic.